Designing Digital Mading Information and Communication System (DMICS) as a Website-based Trusted Information Provider and Management Service - M. Miftach Fakhri; Ainun Zahra Adistia; Jumadil Ahmad Safi’i; Rezka Haris; Awaluddin Yunus (Program Studi Teknik Komputer, 2023)
Technological advancement, today's technical sophistication makes everything easier. The internet is a component of today's technological sophistication. The purpose of this research is to develop a digital magazine system that will facilitate information assistance and the ability to provide information directly through the digital magazine website and play a role in increasing student reading and digital literacy. The development method used in this DMICS design is the agile method. The population used in this study were 48 students and lecturers in Makassar. Data obtained by data collection techniques in the form of literature study and online questionnaire distribution. The designed system is tested using Blackbox Testing to test the function of its features. The results of the study can be concluded that the Digital Mading Information & Communication System (DMICS) can be used as an information container for users. This is indicated from the results of the analysis of each construct has an average value of a good category where each construct of Behavioural Intention to Use (BI), Perceived Enjoyment (PE), Information Quality (IQ), Perceived Usefulness (PU), and System Quality (SQ) obtained a value range of 3.17-3.25. This shows that there is a relationship or influence from the dependent variable, namely, Behavioural intention to use (X1), Perceived enjoyment (X2), Information quality (X3), Perceived usefulness (X4), and System quality (X5) on the independent variable construct, namely actual usage behaviour (Y). Thus, the design of a digital mading information system or Digital Mading Information & Communication System (DMICS) is proven to be good for potential users as a forum for increasing digital literacy.